Association of Serum Vitamin D With Psoriasis and Effect Modification by Central Obesity - Kuang, Yehong; Xiao, Yi; Fang, Zhiqin; Zhang, Yichi; Shen, Minxue; Chen, Xiang; Chen, Mingliang; Lv, Chengzhi; Zhu, Wu (Frontiers in Medicine, 2020)
Background: Psoriasis is a chronic recurrent inflammatory disease with many common mechanisms associated with obesity, such as systemic inflammation and vitamin D deficiency. Among patients with psoriasis, the study aimed to examine the association of serum concentrations of 25-hydroxyvitamin D with psoriasis and the effect modification by obesity. Methods: A mixed cross-section study was conducted. The study consecutively included untreated psoriasis patients from outpatients from the Department of Dermatology of Xiangya Hospital and recruited 205 gendermatched healthy controls from the Hunan Civil Servant Cohort. In both groups, we measured serum 25-hydroxyvitamin D level, body mass index (BMI), waist-hip-ratio (WHR) and other psoriasisrelated clinical indicators. Results: A total of 203 psoriasis outpatients and 205 gender-matched cohort participants with complete data of serum vitamin D concentration were included in the analysis. The serum vitamin D levels were close between the two samples, while the mean WHR of the psoriasis outpatients was significantly higher. Compared with controls, the risk of psoriasis significantly increased when vitamin D decreased from 20 to 10 nmol/L. A significant interaction between serum vitamin D level and obesity categories (BMI× WHR) was identified. After stratification by WHR, vitamin D was not associated with psoriasis in subjects with normal WHR. In contrast, the associations between vitamin D deficiency and psoriasis retained and the effect size augmented among patients with central obesity. Conclusions: WHR may modify the association between serum vitamin D and psoriasis. Treatment advocated for Vitamin D supplyments may tailor to psoriasis with metabolic disorders.